Climate and land use changes will degrade the configuration of the landscape for titi monkeys in eastern Brazil. (14th March 2016) - Gouveia, Sidney F.; Souza‐Alves, João Pedro; Rattis, Ludmila; Dobrovolski, Ricardo; Jerusalinsky, Leandro; Beltrão‐Mendes, Raone; Ferrari, Stephen F.
Abstract: Land use changes have profound effects on populations of Neotropical primates, and ongoing climate change is expected to aggravate this scenario. The titi monkeys from eastern Brazil ( Callicebus personatus group) have been particularly affected by this process, with four of the five species now allocated to threatened conservation status categories. Here, we estimate the changes in the distribution of these titi monkeys caused by changes in both climate and land use. We also use demographic‐based, functional landscape metrics to assess the magnitude of the change in landscape conditions for the distribution predicted for each species. We built species distribution models (SDMs) based on maximum entropy for current and future conditions (2070), allowing for different global circulation models and contrasting scenarios of glasshouse gas concentrations. We refined the SDMs using a high‐resolution map of habitat remnants. We then calculated habitat availability and connectivity based on home‐range size and the dispersal limitations of the individual, in the context of a predicted loss of 10% of forest cover in the future. The landscape configuration is predicted to be degraded for all species, regardless of the climatic settings. This include reductions in the total cover of forest remnants, patch size and functional connectivity. As the landscape configuration should deteriorate severely in the future for all species, the prevention of further loss of populations will only be achieved through habitat restoration and reconnection to counteract the negative effects for these and several other co‐occurring species.